Review: Comparative of monitoring estrus cycle in livestock: Hormonal features and ultrasound - Hasbi Hasbi; Sri Gustina (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2020)
The estrus cycle is a period in which a female animal shows the ability to become pregnant, and this event will continue over some time. The estrus cycle has two different phases, the follicular phase characterized by the presence of graffian follicles which are classified as proestrus and estrus stages or periods from regression of the corpus luteum to ovulation, and luteal phase which is characterized by the presence of the corpus luteum which is classified as the metestrus and diestrus stage or period of ovulation to the corpus luteum regression. Proestrus is chained by decreasing the concentration of progesterone, followed by increasing the concentration of estradiol. Estrus is generally characterized by a very low concentration of progesterone, an increase in the concentration of LH, and a decrease in the concentration of estrogen. Metestrus is characterized by a low concentration of progesterone. Diestrus is characterized by an increase in the concentration of progesterone and an increase in steroid hormone production along with the maturation of the corpus luteum. The purpose of this review is to discuss the comparative monitoring of the estrus cycle in buffalo, dairy cows, sheep and camels related to hormonal features and ultrasonography.